Pathways to literacy - Cairney, Trevor H. (London ; New York : Cassell, 1995)
"This book recognizes that there is no simple way to develop literacy. It begins with the central premise that literacy is not simply a cognitive process; rather, it is a set of social practices that are used in rich sociocultural contexts. Literacy learners come to school with unique social histories that need to be recognized in the programmes devised to facilitate learning. There are many forms of literacy, each with its own specific purposes and contexts in which they are used." "Why is it that school literacy disempowers some, and empowers others? How must schools, teachers and teaching change in order to ensure that literacy can be empowering for all? What types of classroom environments permit children to gain access to the literacy practices which they need to take their place in the world? Addressing these questions provides a refreshingly different look at the many practical classroom strategies and practices necessary to recognize multiple pathways to literacy."--BOOK JACKET.
Includes indexes.
Includes bibliographical references (pages 193-205).
BIED
Complimentary copy from BIED
Keywords: Literacy -- Study and teaching; English language -- Study and teaching; Language arts